Antibiotic-induced photosynthetic dysfunction in wheat: Coupled inhibition of light reactions and carbon assimilation revealed by multi-omics - Jin Wu; Wen Ye; Jiayin Zhou; Yaxin Zhu; Qing Wei; Zhiheng Li; Lidan Wu; Huijun Liu; Shaoting Du (Environmental Pollution, 2026)

R-napropamide drives herbicide-induced cadmium accumulation in Arabidopsis via enantiomer-specific nutrient crosstalk - Yaxin Zhu; Minghui Xie; Haoqi Cui; Ran Wu; Lukuan Huang; Qing Wei; Lijuan Liu; Miaozhen Cai; Shaoting Du (Journal of Environmental Sciences, 2026)

The effect of environmental concern on consumers’ preferences for carbon-neutral-labeled dairy: Evidence from China - Qi Liu; Shaoting Li; Yanjun Ren; Jens-Peter Loy (Journal of Environmental Management, 2026)

Synergistic effects of nitrification inhibitor and ABA-producing Bacteria on cadmium mitigation and quality improvement in Pak choi - Haoqi Cui; Qinghua Ma; Xiaohang Sun; Shumeng Fu; Chengzhi Liu; Lukuan Huang; Ran Wu; Yaxin Zhu; Shaoting Du (Food Chemistry, 2026)

The pulse of ancient fires: Reconstructing Toarcian wildfire regimes from fossil charcoals in northwest China - Yuling Na; Xiao Shi; Chi Tian; Wenpei Pei; Qianqian Song; Shaoting Tian; Bing Wang; Yan Liu; Leon Nahuel Torres; Jianxin Yu (Review of Palaeobotany and Palynology, 2026)

A cleaner production strategy for coalbed methane extraction: Enhancing coal permeability through sodium persulfate oxidation - PengCheng Zhang; Haihui Xin; Jinfeng Wu; Huihui Liu; Shaoting Ju; GuoQing Shi; Bekir Genc; Cheng Zhai (Fuel, 2026)

Trichosanthes kirilowii Maxim. extract ameliorates ulcerative colitis in mice through modulation of metabolic homeostasis and restoration of gut microbiota balance - Shengming Ma; Qian Mao; Shaoting Weng; Zhihui Jiang; Chengwei Zhang; Xiao Liu; Jie Hao; Kunpeng Zhang (Natural Product Research, 2026)

Efficient cellulose evaporator inspired by plant and tumbler for robust solar desalination - Shaoting Chen; Yuqiu Guo; Yalan Liu; Linping Zhang; Wei Wu; Hong Xu; Zhiping Mao (Desalination, 2026)

Zebrafish yolk high phosphoprotein-derived peptide Pt5-1c inhibits methicillin-resistant Staphylococcus aureus by targeting the cell membrane with associated ribosomal perturbation - Yazhuo Zhang; Jia Liu; Gehui Ren; Xueying Liu; Xiangyu Gaochen; Shaoting Shi; Huimin Duan (Fish & Shellfish Immunology, 2026)

CELF2-dependent RNA Regulation Supports Cortical Architecture and Synaptic Stability During Early Brain Development - Ishana Syed; Jing Jiang; Su-Hyuk Ko; Shaoting Chen; Zhao Zhang; Zhijie Liu; Lizhen Chen (Molecular Neurobiology, 2026)

Nano-silicon mitigates sulfamethoxazole-induced stress in wheat seedlings: Integrated transcriptomic and metabolomic analysis - Qianqian Liu; Ziting Jin; Xinyu Liao; Jie Feng; Zhiheng Li; Wenlu Zhao; Yaxin Zhu; Ran Wu; Shaoting Du; Huijun Liu (Journal of Environmental Chemical Engineering, 2025)

Spatiotemporal decoupling of land surface temperature driving mechanisms using ensemble learning - Ai Wang; Daofeng Liu; Zijing Li; Shaoting Liu; Yunfei Nie; Qiang Zhang (Sustainable Cities and Society, 2025)

Herbicide enantiomer selectivity drives soil heavy metal bioavailability: An “Investment-Return” framework in plant-soil-microbe symbiosis - Ran Wu; Hua Wang; Danyang Zou; Mengfei Zhu; Hanche Xia; Yuying Wang; Yaxin Zhu; Lukuan Huang; Lijuan Liu; Shaoting Du (Journal of Hazardous Materials, 2025)

Hidden threat: The high-efficacy herbicidal R-NAP isomer drives heavy metal accumulation in plants via growth stimulation and coordination of metal transporters - Yaxin Zhu; Jiaying Tian; Hanche Xia; Lukuan Huang; Ran Wu; Lijuan Liu; Shaoting Du (Journal of Environmental Management, 2025)

Isolation, evolution, and biological characterization of non-virulent and non-drug-resistant Escherichia coli from porcine intestine - Bingming Ou; Biyang Xiao; Qingqing Li; Jiayi Wang; Xue Lin; Weinan Zhong; Huimin Zhu; Yufu Liu; Shaoting Li; Hongmei Zhang; Wenhua Liu; Minyu Zhang (Folia Microbiologica, 2025)

Single-cell RNA Sequencing Demonstrates the Heterogeneity of Different Molecular Subtypes in Gastric Cancer - Ming Ren; Hongyan Ma; Lijia Guo; Yuqing Liu; Li Wang; Shaoting Wei (Biochemical Genetics, 2025)

Functions of the transcription factor myb-like in sex determination and differentiation in Portunus trituberculatus - Shaoting Jia; Weikang Lan; Yuchao Huang; Yichen Su; Baoquan Gao; Ping Liu; Jianjian Lv (Aquaculture, 2025)

Bacterially mediated carbon-iron coupling drives differential effects of herbicide enantiomers on soil heavy metal bioavailability - Ran Wu; Hua Wang; Hanche Xia; Haoyi Zheng; Yaxin Zhu; Lijuan Liu; Shaoting Du (Soil Biology and Biochemistry, 2025)

Does the herbicide napropamide exhibit enantioselective effects across genus plasmid transfer from Escherichia coli to Bacillus subtilis? - Siyu Zhang; Shihao Zheng; Yanxia Gong; Yin Wang; Qing Wei; Yaxin Zhu; Lijuan Liu; Ran Wu; Shaoting Du (Journal of Hazardous Materials, 2025)

Enhanced mobilization of soil heavy metals by the enantioselective herbicide R-napropamide compared to its S-isomer: Analyses of abiotic and biotic drivers - Hua Wang; Ran Wu; Haoyi Zheng; Yanxia Gong; Yong Yang; Yaxin Zhu; Lijuan Liu; Miaozhen Cai; Shaoting Du (Journal of Hazardous Materials, 2024)

Performance and mechanism analysis of autotrophic denitrification based on FexS - Xinjiao Liu; Shaoting Chen; Rongfang Yuan; Huilun Chen; Beihai Zhou; Shuai Luo (Journal of Cleaner Production, 2024)

Graphene oxide inhibits the transfer of ARGs in rice by reducing the root endophytic bacterial complexity - Ran Wu; Hanche Xia; Yue Wu; Siyu Zhang; Jin Fang; Yuying Wang; Hua Wang; Yaxin Zhu; Lijuan Liu; Shaoting Du (Journal of Environmental Management, 2024)

Effects of sand substrate removal on the intestinal antioxidant and metabolism in Marsupenaeus japonicus - Kuangcheng Zhao; Shaoting Jia; Junxia Wang; Xueqiong Bian; Shibo Chen; Jitao Li; Ping Liu; Jian Li; Yuefeng Cai; Xianyun Ren (Fish & Shellfish Immunology, 2024)

ABA-importing transporter (AIT1) synergies enhances exogenous ABA minimize heavy metals accumulations in Arabidopsis - Yaxin Zhu; Yue You; Shihao Zheng; Jiaxin Li; Yuying Wang; Ran Wu; Zhiguo Fang; Huijun Liu; Shaoting Du (Journal of Hazardous Materials, 2024)

NRT1.2 overexpression enhances the synergistic interplay between ABA-generating bacteria and biochars in reducing heavy metal accumulation in pak choi - Shengtao Wang; Xiaolin He; Jiaying Tian; Ran Wu; Huijun Liu; Zhiguo Fang; Shaoting Du (Science of The Total Environment, 2024)

Environmental fate of microplastics in alpine and canyon-type river-cascade reservoir systems: Large-scale investigation of the Yalong River in the eastern Qinghai-Tibet Plateau - Yixuan Liu; Shaoting Zhao; Dongzhi Wang; Shichen Wang; Xiaofan Ding; Kaiyang Han; Ruiying Wang; Yuyang Kou; Guangqian Zhou; Weibo Shen (Science of The Total Environment, 2024)

Graphene oxide influences transfer of plasmid-mediated antibiotic resistance genes into plants - Ran Wu; Jin Fang; Xiaobo Xiang; Huijun Liu; Yaxin Zhu; Shaoting Du (Science of The Total Environment, 2024)

Degradation of pharmaceuticals in UV/H2O2 process: EEM-based kinetic model, transformation products and corresponding toxicity evaluation - Shaoting Lei; LinChang Guan; Fu Liu; Qingmiao Yu; Ke Xu; Hongqiang Ren; Jinju Geng (Journal of Environmental Chemical Engineering, 2024)

ABA-metabolizing bacteria and rhamnolipids as valuable allies for enhancing phytoremediation efficiency in heavy metal-contaminated soils - Yaxin Zhu; Yu Wang; Huijun Liu; Hua Wang; Minghui Xie; Zhiguo Fang; Shaoting Du (Science of The Total Environment, 2023)

Ketoprofen exposure perturbs nitrogen assimilation and ATP synthesis in rice roots: An integrated metabolome and microbiome analysis - Huan Wang; Zhiheng Li; Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Shaoting Du; Huijun Liu (Environmental Pollution, 2023)

N fertilizers promote abscisic acid-catabolizing bacteria to enhance heavy metal phytoremediation from metalliferous soils - Yaxin Zhu; Yu Wang; Haoyi Zheng; Xiaobo Xiang; Hua Wang; Minghui Xie; Huijun Liu; Zhiguo Fang; Lijuan Liu; Shaoting Du (Science of The Total Environment, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Synergistic interplay between ABA-generating bacteria and biochar in the reduction of heavy metal accumulation in radish, pakchoi, and tomato - Xiaohang Sun; Shengtao Wang; Jiaying Tian; Xiaobo Xiang; Haoyi Zheng; Huijun Liu; Zhiguo Fang; Zhongling Tian; Lijuan Liu; Yaxin Zhu; Shaoting Du (Environmental Pollution, 2023)

Enrichment of cadmium and selenium in soil-crop system and associated probabilistic health risks in black shale areas - Jiawen Zhang; Haoran Guan; Tong Wang; Shaoting Du; Jianming Xu; Xingmei Liu (Environmental Science and Pollution Research, 2023)

Enhanced degradation of pharmaceuticals in wastewater by coupled radical and non-radical pathways: Further unravelling kinetics and mechanism - Fu Liu; Hongzhou Li; Shaoting Lei; Qingmiao Yu; Hongqiang Ren; Jinju Geng (Journal of Hazardous Materials, 2023)

Circ_0101802 Facilitates Colorectal Cancer Progression Depending on the Regulation of miR-665/DVL3 Signaling - Jun Li; Xinbin Liu; Shaoting Dong; Haojie Liao; Weizhen Huang; Xia Yuan (Biochemical Genetics, 2022)

Comparative transcriptomic analysis and validation of the ovary and testis in the ridgetail white prawn (Exopalaemon carinicauda) - Shaoting Jia; Ling Jin; Jianjian Lv; Jiajia Wang; Jitao Li; Ping Liu; Jian Li (Frontiers in Marine Science, 2022)
The ridgetail white prawn, Exopalaemon carinicauda is an important cultured seawater species in China. As female E.carinicauda grows faster than males, it is significant to search for the differentially expressed genes (DEGs) between males and females. However, there is no public available E.carinicauda genome data, and genes related to E. carinicauda sex differences are unclear. In this study, the transcriptome sequencing for ovary and testis tissues of E. carinicauda were conducted, and 20,891 DEGs were identified including 11,709 up-regulated DEGs and 9,182 downregulated DEGs. The functional categories related to meiosis and reproduction were enriched as well as the steroidogenesis KEGG pathway was clustered. Furthermore, the genes related to male reproduction and cell cycle were dug out which were verified by real-time PCR. In addition, two-color fluorescent in situ hybridization result showed that foxj1b might play roles during early stage of the ovary development. Therefore, our result provides clues for the study of genes related to reproduction and sex difference in E.carinicauda .

Ultrahigh Temperature Metamorphic Record of Pelitic Granulites in the Huangtuyao Area of the Huai’an Complex, North China Craton - Shaoting Ma; Xu-Ping Li; Hao Liu; Fanmei Kong; Han Wang (Journal of Earth Science, 2019)